Sustainability Versus Financial Fundamentals: What Investors should Watch in ASEAN Firms - Febriana, Kim Bella; Chan, Felicia Stefanie; Fauzi, Fitriya (International Journal of Energy Economics and Policy, 2026)
This study aims to analyze the influence of sustainability performance, creditworthiness, and capital structure on companies' market value in the ASEAN-6 and to provide practical insights for investors and companies. Balanced panel data from 438 public companies from 2020 to 2024 were obtained from Refinitiv and analyzed using a robust fixed-effects panel data regression approach. This study finds that strong sustainability performance is not adequately rewarded in emerging markets and may even reduce a company's value if it does not deliver economic value. A poor capital structure negatively affects valuation, whereas stronger interest coverage signals financial stability and positively affects Tobin's Q. These findings imply that investors should not rely solely on sustainability scores without examining concrete financial performance evidence. Instead, they are required to monitor a company's ability to service its interest obligations and its debt profile to assess its risk and financial health. Companies are also encouraged to maintain debt at optimal levels, ensure that sustainability efforts create economic value, and maximize operating efficiency to improve market value.